2013
DOI: 10.1371/journal.pone.0076513
|View full text |Cite
|
Sign up to set email alerts
|

IGF-IR Promotes Prostate Cancer Growth by Stabilizing α5β1 Integrin Protein Levels

Abstract: Dynamic crosstalk between growth factor receptors, cell adhesion molecules and extracellular matrix is essential for cancer cell migration and invasion. Integrins are transmembrane receptors that bind extracellular matrix proteins and enable cell adhesion and cytoskeletal organization. They also mediate signal transduction to regulate cell proliferation and survival. The type 1 insulin-like growth factor receptor (IGF-IR) mediates tumor cell growth, adhesion and inhibition of apoptosis in several types of canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 52 publications
1
48
0
Order By: Relevance
“…Quantitative Real Time PCR-Quantitative real time (qRT) PCR analysis was performed as described earlier (37). Each reaction was carried out, at least in triplicate; standard deviations were calculated using Excel (Microsoft) software.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative Real Time PCR-Quantitative real time (qRT) PCR analysis was performed as described earlier (37). Each reaction was carried out, at least in triplicate; standard deviations were calculated using Excel (Microsoft) software.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have indicated that IGF1R stabilizes the molecular structure of β1 integrin by protecting it from proteasomal degradation and promoting tumor cells to grow and proliferate (93). FAK, a substrate protein of IGF1R, is activated by integrin, affecting epithelial transformation, invasion and metastasis of tumor cells IGF1R-independently (38).…”
Section: Interacting With Ecmmentioning
confidence: 99%
“…It is worth noting at this point that the newly identified receptors of CD154 alone or in combination with CD40 could be at play in the CD154-mediated tumorigenic activity. Indeed, the a5b1 and the aMb2 integrins have been described as contributors to the pathogenesis of several types of cancers by interacting with their classical ligands, namely the fibronectin and intercellular adhesion molecule-1 (ICAM-1), respectively [30][31][32][33][34][35][36].…”
Section: Role Of Cd154 In the Pathogenesis Of Cancermentioning
confidence: 99%